Identification of rice samples with rice blast resistance genes Pi-2 and Pi-b - O. V. Shumskaya; N. N. Vozhzhova; O. S. Zhogaleva; Yu. A. Khakhulina; P. I. Kostylev (Зерновое хозяйство России, 2024)
Since rice blast is a disease that causes signiﬁcant damage to rice all over the world, the intensive development of disease-resistant genotypes is of great urgency. The use of molecular biology technologies, new biotechnological approaches and molecular genetic methods allows creating disease-resistant varieties while reducing the time of their development, which plays an important role in growing competitive products. The current paper has highlighted the results of estimating rice samples developed at the FSBSI “ARC “Donskoy” for blast resistance. The objects of the study were new samples developed in the laboratory of rice breeding and seed production. In 2022–2023, there were screened one hundred eighty-seven rice samples. They were identiﬁed on a presence of the blast resistance gene Pi-2. One hundred ﬁfteen samples were estimated for the blast resistance gene Pi-b. Genomic DNA was isolated from young rice leaves. After estimating the quantity and quality of the isolated DNA there was conducted a polymerase chain reaction for the target genes Pi-2 and Pi-b. In order to identify the alleles of the desired genes there were used speciﬁc intragenic molecular SSR markers of dominant (for Pi-2) and codominant (for Pi-b) types. Electrophoresis of the obtained amplicons was performed on 2 % agarose gels during an hour. The results of the analysis were recorded in ultraviolet light and processed in ImageLab 5.1 software. As a result of the conducted study, there were identiﬁed new rice breeding samples that carry blast resistance genes Pi-2 and Pi-b. These samples are recommended for use in the further breeding process for blast resistance.